Effect of betalain extract from bougainvillea (Bougainvillea spectabilis) on the qulaity of pork jerky. - Jabilles, Jona Leth Kim Cameros
The demand for natural food colorants is increasing worldwide due to the negative health issues of synthetic colorants. This study focused on the use of Betalains extracted from Bougainvillea spectabilis as a natural colorant and as potential antimicrobial on pork jerky. BE has undergone spray drying and yielded 2326.7g powder. BE obtained the odor Monarch, pH of 6.54±0.04, %TA of 0.059±0.01, %TSS of 0.60±0.01 and Betalain content of 34.61±1.3 mg/100 g. The betalain powder had the color of Lavender Pink, pH of 5.14±0.01, %TA of 1.24±0.08, %TSS of 9.00±00 and Betalain content of 82.91±0.00 mg/100 g. BP was utilized in the pork jerky formulations which were Formulation A (19 g BP per 125 g pork), Formulation B (24 g BP per 125 g pork) and Formulation C (29 g BP per 125 g pork). Formulation C which was determined as the most preferred formulation (MPJB) was ?liked moderately? and had no significant difference with Control in terms of aroma, texture, chewiness, mouthfeel, taste and color. (p > 0.05). During the 15-day ambient storage, MPJB and Control had increasing pH, aw, and TPC but do not significantly differ (p>0.05). A decrease of 20.47% in the Betalain content of MPJB was observed (p<0.05). MPJB and Control did not exceed the 4 positive-tubes limit in TA detection. Further trials on the effectiveness of betalain as an antimicrobial was recommended.